The Influence of the Internationalization of China Carbon Market on Select Nations Participating in the Belt and Road Initiative - Huang, Guangnan; Leong, Wai Yie (INTI International University, 2025)
The Belt and Road Initiative is a transnational economic cooperation zone led by China, in which China has a strong influence. Due to the backward economic construction of countries along the route, the development of carbon markets varies. In order to increase the international leadership of China's carbon market and influence the global green and low-carbon construction, China needs to accelerate the international development of the carbon market and enhance the international influence of China's carbon market. Based on the theoretical view that the construction of the Belt and Road Initiative builds a bridge for the exchange of emission reduction experience among countries along the route and the construction of imperfect carbon emission trading systems in countries along the route. This paper uses the research methods of literature review and data analysis to illustrate the importance of strengthening the internationalization of China's carbon market through the Belt and Road Initiative policy. In order to increase the international leadership of China's carbon market and influence the global green and low-carbon construction, China needs to accelerate the international development of the carbon market and enhance the international influence of China's carbon market. Actively carrying out carbon trading cooperation with countries along the Belt and Road Initiative will help China build a more internationally influential carbon market and enhance the global influence of China's carbon trading market. Share China's carbon market development and construction experience, accelerate the construction of carbon markets in countries along the Belt and Road Initiative, help countries along the route transform into low-carbon, and promote the establishment of a global carbon trading market and global climate governance system with broad participation, co-construction by all parties, pragmatism and effectiveness, and win-win cooperation.